AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN JOHAR (Cassia siamea Lamk.) TERHADAP Salmonella typhi ATCC 13311 - Isna Jati Asiyah Asiyah; Taufik Turahman (Jurnal Farmasi & Sains Indonesia, 2021)
Salmonella typhi are pathogenic bacterium that are source main cause of typhoid fever. The effort for the treatment of Salmonella typhi bacterial infections is using of antibiotics. However, reports stated that this bacterium having resistance to the chloramphenicol, cotrimoxazole, and amoxicillin antibiotics. Also, the using of antibiotics in the long term have seriously bad effects for the human body that causes disfunction of the liver, kidneys, and heart. The solution can be done to reduce the use of antibiotics is using natural ingredients. Plants that have potential as an antibacterial are johar (Cassia siamea Lamk). This research aims to determine antibacterial activity of ethanol extract johar leaves (Cassia siamea Lamk) against Salmonella typhi along with the value of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The test using diffusion and dilution methods. Extracts are made in 4 variaties concentration: 100%, 75%, 50%, and 25%. Phytochemical tests in this research include test the content of flavonoids, alkaloids, saponins, and tannins. The test results showed that all of the compounds contained in extract johar leaves. The results showed that the ethanol extract of johar leaves have antibacterial activity against Salmonella typhi. The concentration of ethanol extract johar leaves (Cassia siamea Lamk) 100% has the biggest inhibition zone against the growth of Salmonella typhi bacteria with an inhibition zone of 9.9 mm, while the concentration of ethanol extract johar leaves 25% has the lowest inhibition zone diameter of 6 mm. The MIC value of extract johar leaves against Salmonella typhi can not be determined, but the MBC value is 12.5%.